Workshop 8 report: The wider economic, social and environmental impacts of public transport investment. (November 2016) - Mulley, Corinne; Weisbrod, Glen
Abstract: Workshop 8 discussed the measurement of the wider economic, social and environmental impacts of public transport investment and the way in which these measurements could be useful in discussing the ownership and control of land based public transport. Evidence was presented on a micro scale for measuring accessibility and social impacts with discussions centring first, on how these measurements could be useful for operators and authorities in the measurement of market potential and market penetration and second, presenting accessibility measurement as maps could provide the evidence base for identifying service adequacy and identifying the income impacts of public transport planning. In the area of social impacts, papers were presented that looked at the way in which public transport operators can enhance social capital of communities and how new transport infrastructure can generate social capital too. Alongside this came evidence for understanding the causal underpinnings of social impacts through looking at the role of income, personality and preferences in the generation of social benefits. Finally, more macro approaches to examining the wider economic, social and environmental impacts of public transport investment were presented. One of these showed the fuller picture that emerges if an Economic Impact Analysis (EIA) is presented alongside the more usual Cost Benefit Analysis (CBA) since the EIA shows how the economy will respond in terms of jobs, job access and types of jobs which complements the efficiency and welfare approach of CBA. The second showed how incorporating income distributional considerations within a CBA can clearly identify winners and losers. Over and above the detail provided by the evidence in papers, the workshop identified that governments/authorities need to be more explicit and transparent about their objectives and motivations so that operators are clear about what is needed, that governance issues need further debate and that the analysis of risk needs further research and discussion to ensure that better projects are put in place.